2016
DOI: 10.1002/andp.201500352
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic quantum criticality in quasi‐one‐dimensional Heisenberg antiferromagnet

Abstract: We analyze exciting recent measurements [Phys. Rev. Lett. 114 (2015) 037202] of the magnetization, differential susceptibility and specific heat on one dimensional Heisenberg antiferromagnet Cu(C 4 H 4 N 2 )(NO 3 ) 2 (CuPzN) subjected to strong magnetic fields. Using the mapping between magnons (bosons) in CuPzN and fermions, we demonstrate that magnetic field tunes the insulator towards quantum critical point related to so-called fermion condensation quantum phase transition (FCQPT) at which the resulting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…7. These facts support our conclusion that SCQSL of ZnCu 3 (OH) 6 Cl 2 behaves like both the HF electron liquid of YbRh 2 Si 2 and the insulator Cu(C 4 H 4 N 2 )(NO 3 ) 2 [51,52].…”
Section: Thermodynamic Propertiessupporting
confidence: 88%
“…7. These facts support our conclusion that SCQSL of ZnCu 3 (OH) 6 Cl 2 behaves like both the HF electron liquid of YbRh 2 Si 2 and the insulator Cu(C 4 H 4 N 2 )(NO 3 ) 2 [51,52].…”
Section: Thermodynamic Propertiessupporting
confidence: 88%
“…When the magnetic field is larger than the saturation field, dilute magnon behaviour is evidenced by the exponential decay of the susceptibility; III) Using our analytical and numerical results we precisely determine the quantum scalings and magnetic properties of the ideal spin-1/2 antiferromagnet Cu(C 4 H 4 N 2 )(NO 3 ) 2 (denoted by CuPzN for short) [21]. We also find that the magnetization peak used in experiment [21,22,35] is not a good quantity to map out the finite temperature TLL phase boundary. Instead one should use the Wilson ratio or the specific heat peaks.…”
mentioning
confidence: 81%
“…In 1D quantum spin liquid FCQPT plays a role of QCP taking place at H = H s . Here H s is the saturation magnetic field, where QCP occurs, for near QCP taking place at H = H s and T = 0, the fermion spectrum becomes almost flat, and the fermion (spinon) effective mass diverges, M * ∝ M/p F H → ∞, due to kinematic mechanism, since the Fermi momentum p F H → 0 of becoming empty subband [95,96]. In other words, at H = H s both antiferromagnetic sublattices align in the field direction i.e.…”
Section: One-dimensional Quantum Spin Liquid and Other Possible Realimentioning
confidence: 99%
“…As a result, this new state at H > H s is protected by the gap rather than by the Volovik topological number [16,18]. Nonetheless, at elevated temperatures the system bears fingerprints of FC with the behavior very similar to that of HF compounds with approximately flat bands [95,96], including the LFL and NFL regimes. Note that recently a new state of matter, quasi-Fermi liquid, has been introduced by Rozhkov [102] in context of 1D Fermi liquid, while Lebed observed that applicability of Fermi-liquid theory restores in quasi-one-dimensional conductors [103].…”
Section: One-dimensional Quantum Spin Liquid and Other Possible Reali...mentioning
confidence: 99%
See 1 more Smart Citation